2016
DOI: 10.1111/jog.13102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medical institution change on gestational duration after the Great East Japan Earthquake: The Fukushima Health Management Survey

Abstract: Aim: The aim of this study was to examine the association between medical institution change for perinatal care and gestational duration after the Great East Japan Earthquake using data from the Fukushima Health Management Survey. Methods: The data of pregnant women who experienced the earthquake in Fukushima prefecture and participated in the Pregnancy and Birth Survey as part of the Fukushima Health Management Survey were analyzed. The primary and secondary outcomes of this study were gestational duration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…12 Self-referral during pregnancy, which was considered a disaster-related factor, did not affect the duration of gestation in the 2011 data. 14 Further analysis comparing outcomes between pregnancies conceived before and after the disaster is currently ongoing. 15 The incidence of small-for-gestational age infants was affected by neither area in Fukushima nor trimester of pregnancy at the time of the disaster.…”
Section: Resultsmentioning
confidence: 99%
“…12 Self-referral during pregnancy, which was considered a disaster-related factor, did not affect the duration of gestation in the 2011 data. 14 Further analysis comparing outcomes between pregnancies conceived before and after the disaster is currently ongoing. 15 The incidence of small-for-gestational age infants was affected by neither area in Fukushima nor trimester of pregnancy at the time of the disaster.…”
Section: Resultsmentioning
confidence: 99%
“…We noticed an overall decrease in the absolute number of patients admitted in the Obstetrics ward and for reasons related to ‘Pregnancy, childbirth and the puerperium’, of which 94% consists of deliveries, after Haiyan compared to baseline (Tables 1 and 2 ). The evidence about the effects of disasters on pregnancy is mixed: one study suggests that disasters do not influence the gestational period [ 19 ], while another suggests that they can cause preterm labour [ 20 ]. Therefore, we expected the number of deliveries to either remain stable over time or increase within the study period.…”
Section: Discussionmentioning
confidence: 99%
“…They experienced the earthquake between the fourth and 37th weeks of their gestational period. 11 The results showed that pregnant women who changed perinatal checkup institutions due to medical indications had a significantly shorter gestation duration and more preterm births than those who visited only one institution. However, self-referral, which could indicate post-disaster relocation, was not significantly associated with shorter gestation and preterm birth, 11 suggesting that the GEJE and the subsequent accident at the Fukushima Daiichi Nuclear Power Plant did not have a direct impact on gestational duration.…”
Section: Resultsmentioning
confidence: 95%